A Novel 3-Dimensional Printed Nanoceramic Hybrid Resin Fixed Lingual Retainer: Characterization and Mechanical Tests - Noor Salam Alnuaimy; Akram Faisal Alhuwaizi (Hindawi Limited, 2024)
Conclusion: Oval and semielliptical 3D-printed wires offered favorable features as lingual retainers.